Predicting triggering and consequence of delayed LNG RPT. (September 2018) - Aursand, Eskil; Hammer, Morten
Abstract: We develop a model for delayed rapid phase transition (RPT) in LNG spills based on thermodynamics and nucleation theory which includes predictions of both triggering and vapor explosion consequence. We discover that the model predictions can be accurately characterized by two independent parameters alone: The initial fraction of methane and the molar mass of the remaining non-methane part. Based on this we develop correlations for risk assessment which may be used without access to the underlying advanced algorithms, and we give practical advice for risk mitigation. The model is consistent with an often reported empirical triggering criterion for cryogen RPT. We show that spilled LNG must typically boil down to about 10–20% of the original amount before RPT may occur, and after triggering one may expect energy yields of 10–20 g TNT per kg of triggered LNG. Explosive pressures in the range 20–60 bar can be expected. Graphical abstract: Image 1 Highlights: Spilled LNG will likely boil down to about 10–20% of the original amount before triggering RPT vapor explosions. Peak explosive pressures up to about 60 bar is theoretically possible from LNG RPT. Explosive yields can be expected to be 10–20 g TNT per kilogram triggered LNG. LNG RPT consequence may be mitigated by reducing the fraction of propane and butane.